Gleason score as predictor of clinicopathologic findings and biochemical (PSA) progression following radical prostatectomy - Guimaraes,Marbele S. (2008)
OBJECTIVE: There is evidence showing that Gleason grading of prostatic adenocarcinoma is one of the most powerful predictors of biological behavior and one of the most influential factors used to determine treatment for prostate cancer. The aim of the current study was to compare the Gleason score for needle biopsy to the Gleason score for the correspondent surgical specimen, find any possible difference in the biochemical (PSA) progression following surgery in upgraded cases, correlate Gleason score in the specimens to several clinicopathologic variables, and compare outcomes between patients with low-grade vs. high-grade Gleason and Gleason scores 3+4 vs. 4+3. MATERIALS AND METHODS: The study population consisted of 200 consecutive patients submitted to radical prostatectomy. Biochemical progression was defined as PSA > 0.2 ng/mL. Time to PSA progression was studied using the Kaplan-Meier product-limit analysis. RESULTS: In 47.1% of the cases, there was an exact correlation and 40.6% of cases were underestimated in the biopsies. Half of the tumors graded Gleason 6 at biopsy were Gleason score 7 at surgery. These upgraded tumors had outcomes similar to tumors with Gleason score 7 in both biopsy and surgery. There was a positive correlation of high-grade Gleason score in the surgical specimens to higher preoperative PSA, more extensive tumors, positive margins and more advanced pathologic staging. Tumors with a Gleason score > 7 have lower PSA progression-free survival vs. Gleason scores < 7. In this series, there was no significant difference when comparing Gleason scores of 3+4 vs. 4+3. CONCLUSIONS: The findings support the importance of Gleason grading for nomograms, which are used by clinicians to counsel individual patients and help them make important decisions regarding their disease.